Impact of Efficient Resource Management Practices on Sustainable Performance: Moderating Role of Innovative Culture-Evidence From Oil and Gas Firms - Wang, Yihan; Zhang, Shaojie; Xu, Shilin (Frontiers in Psychology, 2022)
The current study analyzed the impact of efficient resource management on consumer resistance and moderating role of innovative culture-. Practitioners and academics have paid close attention to waste, energy, and resource management of oil and gas firms of china on consumer resistance. The present study based on institutional theory that explains the organizational behavior in different perspectives. Data were gathering through a questioner method of 265 manufacturing firms’ managers, employees and workers of oil and gas. The data were analyzed using the “structural equation modeling (SEM)” technique using Smart-PLS for measurement model testing (Cronbach Alpha, composite reliability and discriminant reliability tests) and structural model testing (direct hypothesis testing, moderating test and assessment of R square). The results indicates that components of Waste, Energy, and Resource Management such as CSR, process and equipment, human resource practices, product design and manufacturing planning are positive and significant impact on sustainable performance. In addition, innovative culture plays a moderating role to enhance in firms sustainable performance. Results enhance sustainable performance through Waste, Energy, and Resource Management. Future research can test the conceptual framework of this study in other nations, allowing the conclusions to be more broadly applied. This study brings several key insights for implications along with future research directions are suggested.